Multiscale variability in the Balearic Sea: An altimetric perspective. Issue 6 (17th June 2013) - Mason, Evan; Pascual, Ananda
Abstract : [1] The present‐day availability of an 18 year record of 1 / 8 ° merged Mediterranean Sea sea level anomaly (SLA) data enables a contemporary description of long‐term mesoscale activity in the Balearic Sea. SLA data from satellite altimetry are used to study the variability of sea level and surface geostrophic circulation at different spatial and temporal scales within this complex and relatively understudied region in the western Mediterranean (WMED). We find that the mean Northern Current along the Iberian slope is strongest in autumn, although higher variability in winter leads to stronger peaks in kinetic energy. The Balearic Current, which flows along the northern slopes of the Balearic islands, also has its maximum expression in autumn. Across the two Balearic channels (Ibiza and Mallorca), key locations that partly regulate meridional exchange in the WMED, observed seasonal variability in geostrophic velocity anomalies conforms rather well to prior descriptions, suggesting cautious confidence in the use of the Mediterranean merged altimeter product in nearshore regions. Circulation through the channels is maximum in winter. The channel data support the hypothesis that the channel circulation may be hindered by the intermittent presence of the Western Intermediate Water mass, which sometimes forms in winter in the Gulf of Lions. This is the first time that an analysis of variability in the Balearic channels has been performed using altimetric data. Key Points: Merged altimeter SLA data used to study variability in Balearic Sea. Northern Current strongest in autumn at Ebre slope. First time altimetry used to study variability across Balearic channels.